2014
DOI: 10.1016/b978-0-12-800177-6.00004-9
|View full text |Cite
|
Sign up to set email alerts
|

The UNC-45 Myosin Chaperone

Abstract: UNC-45 is a UCS domain protein that is critical for myosin stability and function. It likely aides in folding myosin during cellular differentiation and maintenance and protects myosin from denaturation during stress. Invertebrates have a single unc-45 gene that is expressed in both muscle and non-muscle tissues. Vertebrates possess one gene expressed in striated muscle (unc-45b) and one that is more generally expressed (unc-45a). Structurally, UNC-45 is composed of a series of alpha-helices connected by loops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 69 publications
1
37
0
Order By: Relevance
“…3). The structure of unc45b protein of grass carp was accordance with that of zebrafish Etard et al 2007;Wohlgemuth et al 2007), and with the UNC-45 protein of C. elegans (Venolia et al 1999;Lee et al 2014) and Drosophila (Lee et al 2011;Lee et al 2014). Those results indicated that the unc45b protein in animals is critical for myosin stability and function.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…3). The structure of unc45b protein of grass carp was accordance with that of zebrafish Etard et al 2007;Wohlgemuth et al 2007), and with the UNC-45 protein of C. elegans (Venolia et al 1999;Lee et al 2014) and Drosophila (Lee et al 2011;Lee et al 2014). Those results indicated that the unc45b protein in animals is critical for myosin stability and function.…”
Section: Discussionsupporting
confidence: 75%
“…The predicted secondary and tertiary structure of unc45b protein of grass carp has a-helix and loops, which were similar to the protein of human, zebrafish and channel catfish, C. elegans (Venolia et al 1999;Lee et al 2014) and Drosophila (Lee et al 2011;Lee et al 2014). This indicated that unc45b protein in different species had high conservation and showed important biological functions such as gene regulation and molecular recognition.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Compared to other tissues, differentiated striated muscle expresses a considerably different complement of molecular chaperones (28,34,(48)(49)(50), presumably to meet its highly specific needs during the final stages of differentiation and for function and tissue homeostasis. For the Hsp90 ensemble, the remodeling is substantial.…”
Section: Discussionmentioning
confidence: 99%
“…UNC-45A is a highly conserved member of the UCS (UNC-45/Cro1/She4p) protein family, which plays a crucial role in chaperone motor protein assembly (18, 19). Our group and others have recently shown that UNC-45A interacts with and affects the folding and stability of myosins including NMIIA via direct binding with myosin heads (19).…”
mentioning
confidence: 99%